Sepsis Neonatorum Awitan Dini - Anastasia - (PT. Kalbe Farma Tbk., 2017)
Sepsis awitan dini tetap menjadi salah satu penyebab paling umum morbiditas dan mortalitas neonatal pada populasi prematur. Identifikasi neonatus berisiko untuk sepsis awitan dini sering didasarkan pada gabungan faktor risiko perinatal yang tidak sensitif maupun spesifik. Pengobatan optimal bayi dengan dugaan awal sepsis adalah agen antimikroba spektrum luas (ampisilin dan aminoglikosida). Setelah patogen diidentifikasi, terapi antimikroba harus disesuaikan. Laporan kasus bayi lahir preterm dgn usia gestasi 25-26 minggu. BBL 1310 gram.Bayi menunjukkan gejala sepsis awitan dini dengan gangguan koagulasi intravaskular diseminata dan trombositopeni. Pemberian antibiotik dimulai dengan antibiotik empiris dan dilanjutkan sesuai hasil kultur. Bayi mengalami perbaikan dan pada kontrol menunjukkan perkembangan yang baik.Early-onset sepsis remains one of the most common causes of neonatal morbidity and mortality among preterm population. The identification of neonates at risk for early-onset sepsis is frequently based on a constellation of perinatal risk factors that are neither sensitive nor specific; and diagnostic tests for neonatal sepsis have a poor positive predictive accuracy. The optimal treatment of infants with suspected early-onset sepsis is broad-spectrum antimicrobial agents (ampicillin and an aminoglycoside). Once a pathogen is identified, antimicrobial therapy should be specified. Antimicrobial therapy should be discontinued after 48 hours if the probability of sepsis is low. This is a case report of preterm infant, gestational age of 25-26 weeks with body weight 1310 grams. The baby showed symptoms of early onset sepsis wih DIC (Disseminated Intravascular Coagulation). Therapy started with empirical antibiotic and continued according to culture results. The baby improved and follow up showed good growth.